Karakteristik Kimia Bokashi dari Kombinasi Limbah Padat Kelapa Sawit dan Feses Ayam dengan Aktivator EM4. (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2026)
This study aims to determine the best combination of oil palm empty fruit bunches (Elaeis guineensis Jacq.) and chicken manure in the production of bokashi fertilizer. The research was conducted in Tanjung Selor from November to December 2025. The method used was nutrient analysis of bokashi fertilizer derived from combinations of oil palm empty fruit bunches and chicken manure with three treatments. The first treatment (P1) consisted of 15 kg of oil palm empty fruit bunches and 10 kg of chicken manure, the second treatment (P2) consisted of 10 kg of oil palm empty fruit bunches and 15 kg of chicken manure, while the third treatment (P3) consisted of 7.5 kg of oil palm empty fruit bunches and 7.5 kg of chicken manure. The parameters observed included nutrient content of bokashi fertilizer, namely Nitrogen (N), Phosphorus (P), Potassium (K), pH, C/N ratio, organic carbon (C-organic), and water content. The results showed that treatment P2, consisting of 10 kg of oil palm empty fruit bunches and 15 kg of chicken manure, produced the best quality bokashi fertilizer.